Boys in care work? - Holtermann, Daniel (Teorija in praksa, 2019)
The professions of EHW (Education, Health and Welfare) are highly segregated and mainly undertaken by women. The question is why this is the case: The theoretical, traditional masculinity and professional habitus of EHW professions is not supportive of boys who are oriented to EHW vocations, although some still choose an EHW career. What leads them to make that decision? Empirical evidence from a survey conducted in Germany with over 3,000 pupils shows the main positive factors impacting boys' EHW vocational orientation are the EHW profession of their parents, the influence of their mothers, and the absence of any focus on technical hobbies. It is concluded that when care and social activities form part of the common lives of male pupils they are much more likely to choose a career in EHW.
Keywords: Enakost spolov; fantje; Gender equality; habitus; Masculinity; Moškost; Occupational choice; Poklicna izbira; skrbstveno delo